The Unity and Fragmentation of Being: Hölderlin’s Metaphysics of Life - Edward Kanterian (Humanities)
Friedrich Hölderlin (1770–1843) is widely known as a poet and sometimes described as a poet’s poet (Heidegger). However, more recent interpretations, undertaken by Dieter Henrich, Michael Franz and others, have shown that he was a genuine philosopher as well, who had an original conception of the relation between art, poetry and metaphysics, with neo-Platonic and theological roots. This paper reconstructs Hölderlin’s ideas and their relation to those of Kant and Fichte. Hölderlin emerges, on the interpretation offered here, as a metaphysician of life, a poet of the biosphere and as such most relevant to our present-day predicament.